2019
DOI: 10.1155/2019/5316984
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin Dietary Supplementation Delays Mouse Ovarian Ageing

Abstract: Advanced maternal age is associated with higher infertility rates, pregnancy-associated complications, and progeny health issues. The ovary is considered the main responsible for these consequences due to a continuous decay in follicle number and oocyte quality. Intracellular imbalance between oxidant molecules and antioxidant mechanisms, in favour of the former, results in oxidative stress (OS) that is believed to contribute to ovarian ageing. This work is aimed at evaluating whether an age-related increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The drug was reported to display antiinflammatory properties in acute lung inflammation [49,50] and in bronchial asthma [51] where oxidative stress was proven to be involved in disease pathogenesis; apocynin reduced ROS concentrations in exhaled breath condensate in asthmatics. More recently, it was demonstrated that dietary supplementation of apocynin ameliorates an age-related increase in ROS and delays mouse ovarian aging [52]. Now, our current study presents for the first time an evidence for beneficial effects of apocynin on isolated in vitro cultured oocytes and eggs.…”
Section: Discussionsupporting
confidence: 55%
“…The drug was reported to display antiinflammatory properties in acute lung inflammation [49,50] and in bronchial asthma [51] where oxidative stress was proven to be involved in disease pathogenesis; apocynin reduced ROS concentrations in exhaled breath condensate in asthmatics. More recently, it was demonstrated that dietary supplementation of apocynin ameliorates an age-related increase in ROS and delays mouse ovarian aging [52]. Now, our current study presents for the first time an evidence for beneficial effects of apocynin on isolated in vitro cultured oocytes and eggs.…”
Section: Discussionsupporting
confidence: 55%
“…The slides were examined and photographed using a Leica CS2 slide scanner system (Leica, Wetzlar, Germany). A follicle containing an oocyte with a distinct nucleus was counted and classified as a primordial, primary, secondary, antral, or atretic follicle according to previously described criteria [ 21 ]. The number of follicles was calculated from the total counts of three representative ovarian midsections of each rat.…”
Section: Methodsmentioning
confidence: 99%
“…OS and inflammation produce synergistic disruptive effects on ovarian tissue. A previous study showed that the levels of the products of OS damage (carbonylated and nitrated proteins) and inflammatory markers (TNF-α, IL-1β) were significantly higher in the ovaries of aged mice than in younger mice [ 39 ]. Ovarian RNA transcriptome analysis further revealed that OS-related proteins (Nrf2, SOD2, CAT, GSH-px1) and genes encoding NLRP3 inflammatory vesicles could be used as key biomarkers to differentiate between young and aging mice [ 40 ].…”
Section: Pathological Mechanisms Related With Os In Ovarian Agingmentioning
confidence: 99%